Copper pipe, heat transfer pipe, refrigerant piping, air conditioner and refrigerator

JP2025024273APending Publication Date: 2025-02-20NJT COPPER TUBE CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023128259
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-20

AI Technical Summary

Benefits of technology

【0022】 本発明によれば、SCCに対する耐食性を維持しつつ、蟻の巣状腐食に対する耐食性に優れる銅管を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024273000001_ABST
    Figure 2025024273000001_ABST
Patent Text Reader

Abstract

To provide a copper pipe that exhibits enhanced resistance to ant's nest-like corrosion while maintaining its corrosion resistance to SCC.SOLUTION: A copper pipe is composed of a copper material that contains 0.004-0.040 wt.% of P with the balance being Cu and unavoidable impurities. The copper pipe has, on its external surface, a copper oxide coating with a total thickness of 50-100 nm. Within a depth range of up to 3 nm from the outermost position of the copper oxide coating, the CuO proportion is 25 mol% or more. The total proportion of CuO and Cu(OH)2 is 90 mol% or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a corrosion-resistant copper tube, and in particular to a copper tube that is suitably used for heat transfer tubes and refrigerant piping in air conditioners and refrigeration equipment, and that has excellent corrosion resistance against ant nest corrosion and stress corrosion cracking (SCC). [Background technology]

[0002] Traditionally, phosphorus (P) deoxidized copper tubes (JIS-H3300-C1220T) have been primarily used for pipe materials such as heat transfer tubes in air conditioners and refrigerant piping (internal piping) in refrigeration equipment, due to their excellent corrosion resistance, brazability, thermal conductivity, and bending workability.

[0003] Phosphorus-deoxidized copper tubes, which are used in air conditioners and refrigeration equipment, can develop an abnormal corrosion that progresses in an ant nest-like pattern from the tube surface in the direction of the tube thickness, known as ant nest corrosion. This ant nest corrosion is said to occur in a wet environment with low-grade carboxylic acids such as formic acid and acetic acid as the corrosive agent. Similar corrosion has also been confirmed in environments containing chlorine-based organic solvents such as 1,1,1-trichloroethane, certain types of lubricating oil, formaldehyde, etc.

[0004] It is known that the occurrence of ant nest corrosion is particularly noticeable when the copper pipe is used as a piping where condensation occurs in air conditioners or freezers. Once such ant nest corrosion occurs, the corrosion progresses quickly and penetrates the copper pipe in a short period of time, causing the problem that the equipment cannot be used.

[0005] For this reason, Patent Document 1 proposes a highly corrosion-resistant copper tube that contains 0.05 to 1.0% by weight of P (phosphorus) and the remainder is made of a Cu material that is an inevitable impurity, and it is made clear that this improves corrosion resistance against ant nest corrosion. In other words, it points out the fact that it is possible to practically and advantageously obtain a copper tube that has even improved corrosion resistance against ant nest corrosion in a region with a high P content compared to conventional tube materials made of phosphorus deoxidized copper.

[0006] Moreover, Patent Document 2 reveals that by setting the crystal grain size to 0.005 to 0.050 mm, the corrosion resistance against ant nest corrosion can be further effectively improved. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2014 / 148127 [Patent Document 2] International Publication No. 2018 / 061270 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the copper tubes of Patent Documents 1 and 2 have a problem in that stress corrosion cracking (hereinafter referred to as SCC) may occur when stress is applied in an ammonia environment.

[0009] On the other hand, low phosphorus copper material with P; 0.001-0.004% by weight and so-called phosphorus deoxidized copper with P; 0.004-0.040% by weight (P; 0.004-0.015% by weight; low phosphorus deoxidized copper; JIS H3300 C1020, P; 0.015-0.040% by weight; high phosphorus deoxidized copper; JIS H3300 C1220) have been said to have low stress corrosion cracking susceptibility, but have low ant nest corrosion inhibition effect. Patent Document 2 describes that, in copper alloy tubes containing the same concentration of P, if the segregation of P in a micro area on the outer surface of the tube is lower than a certain standard, the ant nest corrosion inhibition effect is superior compared to those that do not, but a high phosphorus deoxidized copper tube with a P concentration of 0.015-0.040% by weight does not actually obtain the ant nest corrosion inhibition effect.

[0010] Therefore, there is a demand for the development of copper tubes that are excellent in corrosion resistance against ant nest corrosion and excellent in corrosion resistance against SCC.

[0011] Therefore, an object of the present invention is to provide a copper tube that has excellent corrosion resistance against ant nest corrosion while maintaining corrosion resistance against SCC. [Means for solving the problem]

[0012] In light of the above technical background, the present inventors conducted extensive research and found that by carrying out the final heat treatment in the manufacture of a copper tube in a slightly oxidizing atmosphere, it is possible to form an extremely thin copper oxide film having an appropriate Cu oxide composition on the outer surface of the copper tube, and that a copper tube having such a copper oxide film formed thereon has excellent corrosion resistance against ant nest corrosion while maintaining corrosion resistance against stress corrosion cracking (SCC), thereby completing the present invention.

[0013] That is, the present invention (1) comprises a copper material containing 0.004 to 0.040% by weight of P, with the balance being Cu and unavoidable impurities; The outer surface of the copper tube has a copper oxide film with a total thickness of 50 to 100 nm. the proportion of CuO in the copper oxide film within a range from the outermost position to a depth of 3 nm is 25 mol % or more, and the sum of the proportions of CuO and Cu(OH)2 is 90 mol % or more; The present invention provides a copper tube characterized by the above.

[0014] The present invention (2) provides the copper tube according to (1), characterized in that, in the range from the outermost position of the copper oxide film to a depth of 30 nm, the proportion of Cu2O is 85 mol% or more and the proportion of CuO is 10 mol% or more.

[0015] The present invention (3) provides a copper tube according to (1) or (2), characterized in that the copper tube is placed in a wet environment and is exposed to a corrosive agent consisting of a lower carboxylic acid, the corrosion occurring in an ant nest-like pattern from the surface of the tube in the thickness direction of the tube.

[0016] The present invention (4) also provides a heat transfer tube comprising the copper tube of any one of (1) to (3) and used as a heat transfer tube for air conditioning equipment or refrigeration equipment.

[0017] The present invention (5) also provides a refrigerant pipe comprising the copper pipe of any one of (1) to (3) and used for refrigerant pipe of an air conditioner or a refrigeration device.

[0018] The present invention (6) also provides an air conditioner comprising the heat transfer tube of (4).

[0019] The present invention (7) also provides a refrigeration device comprising the heat transfer tube of (4).

[0020] The present invention (8) also provides an air conditioner having the refrigerant pipe according to (5).

[0021] The present invention (9) also provides a refrigeration device having the refrigerant pipe according to (5). Effect of the Invention

[0022] According to the present invention, it is possible to provide a copper tube that has excellent corrosion resistance against ant nest corrosion while maintaining corrosion resistance against SCC. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 is a schematic cross-sectional view for illustrating a copper oxide film formed on the copper tube of the present invention. [Diagram 2] FIG. 2 is a diagram showing a test apparatus for carrying out a ant nest corrosion test in the examples. [Diagram 3] FIG. 2 is a diagram showing a test apparatus for carrying out a stress corrosion cracking test in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The copper tube of the present invention is made of a copper material containing 0.004 to 0.040% by weight of P, with the remainder being Cu and unavoidable impurities; The outer surface of the copper tube has a copper oxide film with a total thickness of 50 to 100 nm. the proportion of CuO in the copper oxide film within a range from the outermost position to a depth of 3 nm is 25 mol % or more, and the sum of the proportions of CuO and Cu(OH)2 is 90 mol % or more; This is a copper tube characterized by the above.

[0025] The copper tube of the present invention has a copper oxide film on its outer surface. FIG. 1 is a schematic cross-sectional view for explaining the copper oxide film formed on the copper tube of the present invention, showing the vicinity of the outer surface. The copper tube 1 has a copper oxide film 2 on its outer surface. That is, the copper tube 1 has the copper oxide film 2 formed in the range from the outermost position 3 to the innermost position 4 of the copper oxide film 2. The outermost position 3 of the copper oxide film 2 is the boundary position between the copper oxide film and the outside air, and the innermost position 4 of the copper oxide film 2 is the boundary position between the copper oxide film and the copper base. In FIG. 1, the range indicated by the reference numeral 5 is the range from the outermost position 3 of the copper oxide film 2 to a depth position 8 at a depth of 3 nm, and the range indicated by the reference numeral 6 is the range from the outermost position 3 of the copper oxide film 2 to a depth position 9 at a depth of 30 nm. The total thickness of the copper oxide film 2 refers to the distance from the outermost position 3 of the copper oxide film 2 to the innermost position 4 of the copper oxide film 2.

[0026] The copper tube of the present invention is made of a copper material containing 0.004-0.040% by weight of P, with the remainder being Cu and unavoidable impurities. That is, the copper tube of the present invention is formed of a copper material containing 0.004-0.040% by weight of P, with the remainder being Cu and unavoidable impurities. Examples of the copper material forming the copper tube of the present invention include conventional copper materials such as JIS H3300 C1220 (P content: 0.0015-0.040% by weight) and JIS H3300 C1201 (P content: 0.004-0.015% by weight).

[0027] The copper tube of the present invention has a copper oxide film on the outer surface of the copper tube. In the present invention, the outer surface of the copper tube refers to the outer surface of the copper tube. The copper oxide film is composed of Cu2O, CuO, and Cu(OH)2. The total thickness of the copper oxide film is 50 to 100 nm, preferably 60 to 80 nm. By having the total thickness of the copper oxide film in the above range, the corrosion resistance against ant nest corrosion is excellent while maintaining the corrosion resistance against SCC. On the other hand, if the total thickness of the copper oxide film is less than the above range, the corrosion resistance against SCC and the corrosion resistance against ant nest corrosion are inferior, and if it exceeds the above range, the color tone of the copper tube outer surface becomes purple to dark green, and there is a risk of cracks occurring on the outer surface during bending and tube expansion.

[0028] In the copper tube of the present invention, Cu2O, CuO, and Cu(OH)2 are present throughout the copper oxide film, but Cu2O is predominant in the deep layers, Cu(OH)2 is predominant near the outer surface, and CuO is predominant in the intermediate portion between the deep layers and the outer surface, forming a copper oxide film. In the copper tube of the present invention, the presence of a large amount of Cu2O in the deep layers of the copper oxide film makes the copper oxide film dense, and it exhibits a basic blocking effect against corrosive media containing acids and alkalis, water, and oxygen, and at the same time, when an aqueous solution of a corrosive media containing acids and alkalis penetrates, part of the copper oxide film dissolves, thereby exhibiting an effect of buffering the oxidizing power of the media, resulting in a corrosion-resistant (excellent corrosion-resistant) film.

[0029] In the copper tube of the present invention, the proportion of CuO in the range from the outermost position of the copper oxide film to a depth of 3 nm is 25 mol % or more, and the sum of the proportions of CuO and Cu(OH)2 is 90 mol % or more.

[0030] The proportion of CuO in the area from the outermost position to a depth of 3 nm of the copper oxide film is 25 mol % or more, and preferably 35 to 55 mol %. When the proportion of CuO in the area from the outermost position to a depth of 3 nm of the copper oxide film is in the above range, the copper oxide film has excellent corrosion resistance against ant nest corrosion while maintaining corrosion resistance against SCC.

[0031] The total of the proportions of CuO and Cu(OH)2 in the range from the outermost position of the copper oxide film to a depth of 3 nm is 90 mol% or more, preferably 95 mol% or more. When the total of the proportions of CuO and Cu(OH)2 in the range from the outermost position of the copper oxide film to a depth of 3 nm is in the above range, the copper oxide film has excellent corrosion resistance against ant nest corrosion while maintaining corrosion resistance against SCC.

[0032] The proportion of Cu(OH)2 in the range from the outermost position to a depth of 3 nm of the copper oxide film is preferably 40 to 65 mol%. The Cu(OH)2 in the range from the outermost position to a depth of 3 nm of the copper oxide film is crystalline, and when the moisture absorbed when the outer surface of the copper tube is exposed to the outside air passes through the gaps of the crystalline Cu(OH)2 in the copper oxide film near the outer surface and reaches the middle part, it causes a reaction with CuO in the middle part to "CuO + H2O → Cu(OH)2". In either case of exposure to a formic acid atmosphere or an ammonia atmosphere, which are corrosive environments, the gaps near the initial outer surface are blocked by the newly generated crystalline Cu(OH)2, which has the effect of blocking the intrusion of moisture.

[0033] In the copper tube of the present invention, the density of the copper oxide film in the shallow layers (near the outer surface, middle parts) is somewhat lower than that of the deeper layers, which are mainly composed of Cu2O. However, the presence of a certain proportion of CuO promotes the capture of corrosive media, including acids and alkalis, when they penetrate through the gaps in the crystalline Cu(OH)2 in the copper oxide film near the outer surface. At the same time, the dissolution of part of the copper oxide film acts to buffer the oxidizing power of the corrosive media, providing a corrosion-resistant protective film.

[0034] In the copper tube of the present invention, it is preferable that the proportion of Cu2O in the range from the outermost position of the copper oxide film to a depth of 30 nm is 85 mol % or more and the proportion of CuO is 10 mol % or more.

[0035] The proportion of Cu2O in the range from the outermost position of the copper oxide film to a depth of 30 nm is preferably 85 mol% or more, more preferably 90 mol% or more. By having the proportion of Cu2O in the range from the outermost position of the copper oxide film to a depth of 30 nm being within this range, the copper oxide film has excellent corrosion resistance against ant nest corrosion while maintaining corrosion resistance against SCC.

[0036] The proportion of CuO in the area from the outermost position to a depth of 30 nm of the copper oxide film is preferably 10 mol % or more, and more preferably 11 to 15 mol %. When the proportion of CuO in the area from the outermost position to a depth of 30 nm of the copper oxide film is in the above range, the copper oxide film has excellent corrosion resistance against ant nest corrosion while maintaining corrosion resistance against SCC.

[0037] The total of the proportions of Cu2O and CuO in the area from the outermost position of the copper oxide film to a depth of 30 nm is preferably 98 mol% or more. By having the total of the proportions of Cu2O and CuO in the area from the outermost position of the copper oxide film to a depth of 30 nm within the above range, corrosion resistance against ant nest corrosion is excellent while maintaining corrosion resistance against SCC.

[0038] The tensile strength (σB) of the copper tube of the present invention is preferably 205 MPa or more, particularly preferably 215 to 240 MPa. The 0.2% proof stress (σ0.2) of the copper tube of the present invention is preferably 50 MPa or more, particularly preferably 60 to 85 MPa. The elongation (δ) of the copper tube of the present invention is preferably 40% or more, particularly preferably 45 to 55%.

[0039] A manufacturing example of the copper tube of the present invention will be described below. Note that the manufacturing example of the copper tube of the present invention described below is one example for manufacturing the copper tube of the present invention, and the copper tube of the present invention is not limited to the one manufactured by the method described below.

[0040] The copper tube of the present invention is manufactured by casting a copper ingot of a specified chemical composition, followed by various processing and heat treatments. The inventors have discovered that by performing the final heat treatment under appropriate conditions, it is possible to form an extremely thin layer of a copper oxide film having a suitable copper oxide composition on the outer surface of the copper tube, and that the presence of such a copper oxide film makes it possible to obtain a copper tube that has excellent corrosion resistance to ant nest corrosion while maintaining corrosion resistance to stress corrosion cracking (SCC).

[0041] The method for producing a copper tube of the present invention is characterized by comprising at least a casting step, hot working, cold working such as cold rolling and cold drawing, and final heat treatment.

[0042] In the method for producing a copper tube of the present invention, first, a casting step is performed in which melting and casting are performed according to a conventional method to obtain a copper ingot (billet) containing 0.004 to 0.040 wt % P with the remainder being Cu and unavoidable impurities.

[0043] Next, in the manufacturing method of the copper tube of the present invention, the copper ingot (billet) is heated and hot worked, and then cold worked to a desired shape. The hot working is generally hot extrusion. Examples of cold working include cold rolling, cold drawing, and rolling to form an inner groove. In any of the cold working methods exemplified above, in the process of working to the final dimensions, a long coil of several hundred to several thousand meters is generally formed while reducing the outer diameter and wall thickness.

[0044] In the method for producing a copper tube of the present invention, a heat treatment (intermediate annealing) can be appropriately performed before cold working, between passes of cold working, etc.

[0045] Finally, in the method for producing a copper tube of the present invention, a final heat treatment is performed. In the final heat treatment, the copper material that has been work-hardened by cold working is heated and held at a temperature equal to or higher than the recrystallization temperature, thereby tempering the material so that its strength and elongation are suitable for the subsequent processing.

[0046] The final heat treatment may be performed using an induction heating furnace, a roller hearth heating furnace, a batch heating furnace, or the like. However, in the method for producing a copper tube of the present invention, in order to form a copper oxide film having a suitable copper oxide composition on the outer surface of the copper tube after the final heat treatment, it is necessary to appropriately control the atmosphere gas in the final heat treatment. That is, the atmosphere gas in the final heat treatment is an atmosphere gas with an O2 concentration of 0.08 to 0.20 volume % and the remainder being an inert gas such as N2 or Ar, in which the copper tube is subjected to slight oxidation annealing and cooled in the atmosphere. In preparing the atmosphere gas, O2 gas is dehumidified to a relative humidity of less than 10% and mixed with an inert gas such as N2 or Ar. In addition, reducing gases such as CO and H2 reduce the copper oxide film on the outer surface of the copper tube that has been generated, so reducing gases such as CO and H2 are not used in the final heat treatment according to the method for producing a copper tube of the present invention.

[0047] In the method for producing a copper tube of the present invention, a copper oxide coating having the copper oxide composition specified for the copper tube of the present invention can be formed by carrying out the final heat treatment according to the method for producing a copper tube of the present invention.

[0048] The copper tube of the present invention and the copper tube obtained by carrying out the manufacturing method of the copper tube of the present invention are suitable for use as copper tubes that are placed in a humid environment and exposed to a corrosive action that progresses in an ant nest-like manner from the tube surface in the tube thickness direction by a corrosive medium consisting of a low carboxylic acid. The copper tube of the present invention and the copper tube obtained by carrying out the manufacturing method of the copper tube of the present invention are excellent in corrosion resistance against ant nest-like corrosion and in corrosion resistance against SCC, even when placed in a humid environment and exposed to a corrosive action that progresses in an ant nest-like manner from the tube surface in the tube thickness direction by a corrosive medium consisting of a low carboxylic acid, and therefore the life of the copper tube and the heat exchanger in which the copper tube is used can be extended.

[0049] The heat transfer tube of the present invention is made of the copper tube of the present invention or a copper tube obtained by the manufacturing method of the copper tube of the present invention, and is a copper tube for use as a heat transfer tube in an air conditioner or a refrigeration device. That is, the heat transfer tube of the present invention is a heat transfer tube used in an air conditioner or a refrigeration device, and is used as a heat transfer tube constituting a heat exchanger of the air conditioner or the refrigeration device.

[0050] The refrigerant pipe of the present invention is made of the copper pipe of the present invention or a copper pipe obtained by the manufacturing method of the copper pipe of the present invention, and is a copper pipe for refrigerant pipe of an air conditioner or a refrigeration equipment. That is, the refrigerant pipe of the present invention is used as a refrigerant pipe through which a refrigerant flows in an air conditioner or a refrigeration equipment.

[0051] The air conditioner of the present invention has the heat transfer tube of the present invention, that is, a heat transfer tube made of the copper tube of the present invention or a copper tube obtained by the method for producing a copper tube of the present invention.

[0052] The refrigeration equipment of the present invention has the heat transfer tube of the present invention, that is, a heat transfer tube made of the copper tube of the present invention or a copper tube obtained by the copper tube manufacturing method of the present invention.

[0053] The air conditioner of the present invention has the refrigerant piping of the present invention, that is, the refrigerant piping made of the copper tube of the present invention or the copper tube obtained by the method for producing a copper tube of the present invention.

[0054] The refrigeration equipment of the present invention has the refrigerant piping of the present invention, that is, the refrigerant piping made of the copper tube of the present invention or the copper tube obtained by the copper tube manufacturing method of the present invention.

[0055] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples. EXAMPLES

[0056] Example 1 <Composition of copper tube> Chemical composition: Contains 0.027% by weight of P, the balance being Cu and unavoidable impurities <Manufacturing process> (1) Casting process A billet was prepared with a chemical composition containing 0.027 wt % P, with the remainder being Cu and unavoidable impurities. (2) Hot processing The billet obtained above was heated to 850° C., then hot extruded and quenched to obtain an extruded raw pipe. (3) Cold working The extruded raw pipe obtained above was cold rolled and coiled up by the first cold drawing process. Next, the cold drawing process was repeated several times to draw it to a diameter of 7 mm and a wall thickness of 0.40 mm. After drawing, it was wound using a drum winding machine into a long coil with an outer diameter of 900 mm, an inner diameter of 560 mm, and a coil width of 230 mm. (4) Final heat treatment The long coil thus obtained was subjected to a final heat treatment to obtain a soft copper tube having an outer diameter of 7 mm and a wall thickness of 0.40 mm. The final heat treatment furnace and conditions are as follows: Heat treatment furnace (type): Batch annealing furnace Heat treatment conditions (temperature, time): Maximum temperature 450℃ x holding time 1 hour Atmosphere gas in heat treatment furnace: O2 concentration 0.08 to 0.20 volume percent, balance N2

[0057] Comparative Example 1 The final heat treatment furnace and conditions were the same as in Example 1, except that the atmospheric gas in the heat treatment furnace was changed from an O2 concentration of 0.08 to 0.20 volume percent and the balance N2 to an O2 concentration of 300 volume ppm or less (0.03 volume percent or less), CO and H2 concentrations of 1.0 to 35 volume percent, and the balance N2.

[0058] <Analysis of copper oxide film> Copper tubes (Example copper tubes 1A and 1B) were taken from two different positions of the long copper tube coil produced in Example 1. Copper tubes (Comparative copper tubes 1a and 1b) were taken from two different positions of the long coil produced in Comparative Example 1. Next, the properties (composition) of the copper oxide film of each copper tube were analyzed by the following analytical method. The results are shown in Table 1.

[0059] <Method for evaluating the total thickness of a copper oxide film> The samples taken from each copper tube were processed by FIB from the outer surface, the evaluation area was picked up, and sliced ​​to about 0.1 μm, after which the total thickness of the copper oxide film was measured by STEM observation of the tube circumferential cross section and EDS analysis. In preparing the samples, a C film and a W film were formed as protective films on the outer surface of the samples. The specifications of the analysis device are as follows. -FIB (Focused Ion Beam Processing Machine): Hitachi High-Tech Science NX2000 TEM / STEM (transmission / scanning transmission electron microscope): FEI TalosF200X -Method of measuring copper oxide film: STEM bright field images (BF) and high angle dark field images (HAADF) were taken at 5 points at 20 nm intervals over an arbitrary 100 nm width on the observation cross section, and the copper oxide film thickness was measured at each point while comparing the contrast between the two, and the average value was used as the representative value. Element mapping data from EDS analysis was also referenced for the boundary position between the copper oxide film and the copper base material.

[0060] <Method for analyzing the composition of the copper oxide film in the range from the outermost position to a depth of 3 nm> The bonding state of Cu and O was analyzed by XPS (X-ray photoelectron spectroscopy), and Cu2p 3 / 2 The spectrum was measured and waveform separation was performed to calculate the composition ratio of Cu2O, CuO, and Cu(OH)2. Equipment: PHI Quantera SXM X-ray source / X-ray output / analysis area: Single crystal spectroscopic Al_Kα line / 25.0W / Φ100μm ·Pass Energy: Wide Scan-280.00eV(1.00eV / Step) Narrow Scan-69.00eV(0.125eV / Step) - Electrostatic neutralization gun: Ar+, e- used Geometry: θ=45deg. (angle between sample surface and detector)

[0061] <Method for analyzing the composition of the copper oxide film in the range from the outermost position to a depth of 30 nm> The bonding state of Cu and O was analyzed by HAXPES (hard X-ray photoelectron spectroscopy), and Cu2p 3 / 2 The spectrum was measured and waveform separation was performed to calculate the composition ratio of Cu2O, CuO, and Cu(OH)2. Excitation X-ray source: SPring-8 BL09XU beamline (double crystal monochromator) hv=7940.02eV (Au4f standard sample) 7 / 2= 84.00 eV) ·Pass Energy: 100eV, slit0.3mm(straight) ·Vacuum degree<1.0×10 -6 Pa ΔE<200meV (calculated from the width of the Au Fermi edge) Photoelectron detection angle: Around 90 deg. Beam size: Approx. H2μm x Approx. W20μm Attenuator: Al_50μm+Si_100μm ·KB mirror: Yes (one defocused position)

[0062] <Corrosion resistance evaluation results> The evaluation of ant nest corrosion and stress corrosion cracking (SCC) was carried out using the evaluation methods shown below. The results are shown in Table 1.

[0063] <Ant nest corrosion test and evaluation method> For the various copper tubes prepared, an ant nest corrosion test was carried out using a test device shown in Figure 2. In Figure 2, 12 is a 2L plastic container that can be sealed with a cap 14, and a test copper tube 10 is inserted into the plastic container 12 so as to penetrate a silicone plug 16 attached to the cap 14. A pressure sensor 11 is attached to one side of the test copper tube 10, and the lower end opening of the test copper tube 10 is blocked with a silicone plug 18. Here, the test copper tube 10 has a length of 18 cm, and the length of the part exposed in the plastic container 12 is 15 cm. In addition, 100 ml of a formic acid solution of a predetermined concentration is contained in the plastic container 12 in a form that does not contact the test copper tube 10. Nitrogen gas was introduced through the nitrogen introduction pipe 13 and a leak check was performed under a load of 1.0 MPa to confirm the airtightness inside the pipe in advance. In the ant nest corrosion test, the concentration of the formic acid solution 15 was set to 0.1%, and the specified test copper tube 10 was set in the plastic container 12 containing the formic acid solution 15, and the plastic container 12 was left in a thermostatic chamber at 40°C, and was then taken out of the chamber for 2 hours / day and kept at room temperature (15°C), so that the temperature difference promoted condensation on the surface of the test copper tube 10. Under such conditions, the internal pressure was monitored by a sensor. The time until the internal pressure became 0.8 MPa or less was measured as the penetration time. When the penetration time was 720 hours or more, the corrosion resistance was excellent and was marked with "◯", and when it was less than 720 hours, the corrosion resistance was poor and was marked with "×".

[0064] <Stress corrosion cracking (SCC) testing and evaluation methods> For each type of copper pipe prepared, an exposure test (SCC evaluation test) was carried out in an ammonia atmosphere using the test equipment shown in Figure 3. In Figure 3, 22 is a 2 L plastic container that can be sealed with a cap 24, and the test copper tube 21 is inserted into the plastic container 22 so as to penetrate a silicone plug 26 that is attached by penetrating the cap 24. The test copper tube 21 was φ7 mm × t0.40 mm, and a pressure sensor 25 was attached to one end of the test copper tube 21, and the other end was sealed by brazing. The test copper tube 21 was bent into a U-shape, and shrink tubes 28 were placed over two points located inside the container, and these two points were fixed with glass tape 29. Silicon masking 30 was applied to the surface of the test copper tube 21 between the silicon plug 26 and the shrink tube 28. Nitrogen gas was introduced through the nitrogen introduction pipe 27 and a leak check was performed under a load of 4.0 MPa to confirm the airtightness inside the pipe in advance. 200 ml of 1 vol. % aqueous ammonia solution 23 was placed in the bottom of the test vessel 22, and the test copper tube 21 was exposed to the gas layer, and the internal pressure was monitored by a sensor. The time until the internal pressure became 3.8 MPa or less was measured as the penetration time. When the penetration time was 720 hours or more, the corrosion resistance was excellent and was marked with "◯", and when it was less than 720 hours, the corrosion resistance was poor and was marked with "×".

[0065] [Table 1]

[0066] The descriptions in Table 1 are as follows: Outermost position to 3 nm: Range from the outermost position of the copper oxide film to a depth of 3 nm Outermost position to 30 nm: Range from the outermost position of the copper oxide film to a depth of 30 nm Total thickness: Total thickness of copper oxide film CuO: CuO ratio Ratio of Cu(OH)2:Cu(OH)2 Cu2O:Cu2O ratio CuO+Cu(OH)2: The sum of the proportions of CuO and Cu(OH)2 Cu2O+CuO: The sum of the proportions of Cu2O and CuO

[0067] <Ant nest corrosion test results> An ant nest corrosion test was conducted on Example Copper Tubes 1A and 1B of Example 1, which used copper tubes with a P content of 0.027% by weight. As a result, no penetration occurred in any of the tubes within 720 hours, and the tubes were rated as ◯. In addition, an ant nest corrosion test was conducted on comparative copper tubes 1a and 1b of Comparative Example 1, which also used copper tubes with a P content of 0.027% by weight. As a result, penetration occurred in both tubes within 720 hours, and the tubes were rated as ×.

[0068] <Stress corrosion cracking (SCC) test results> A stress corrosion cracking test was carried out on Example Copper Tubes 1A and 1B of Example 1, which used copper tubes with a P content of 0.027% by mass. As a result, no penetration occurred in any of the tubes within 720 hours, and the tubes were rated as ◯. In addition, a stress corrosion cracking test was conducted on comparative copper tubes 1a and 1b of Comparative Example 1, which also used copper tubes with a P content of 0.027% by mass. As a result, perforation occurred in both tubes within 720 hours, and the tubes were rated as ×. [Explanation of symbols]

[0069] 1 copper tube 2. Copper oxide film 3 Outermost position of copper oxide film 4. Innermost position of copper oxide film 5. The area from the outermost position of the copper oxide film to a depth of 3 nm 6. The area from the outermost position of the copper oxide film to a depth of 30 nm 8 30 nm deep from the outermost position of the copper oxide film 9 3 nm depth from the outermost position of the copper oxide film

Claims

1. The copper material contains 0.004 to 0.040 wt % of P, with the balance being Cu and unavoidable impurities; The outer surface of the copper tube has a copper oxide film having a total thickness of 50 to 100 nm. The proportion of CuO in the range from the outermost position of the copper oxide film to a depth of 3 nm is 25 mol % or more, and the proportion of CuO and Cu(OH) 2 The total proportion of is 90 mol % or more; The copper pipe is characterized by:

2. Cu in the range from the outermost position of the copper oxide film to a depth of 30 nm 2 2. The copper tube according to claim 1, characterized in that the proportion of O is 85 mol % or more and the proportion of CuO is 10 mol % or more.

3. 3. The copper tube according to claim 1 or 2, characterized in that the copper tube is placed in a humid environment and is exposed to a corrosive action of a corrosive medium comprising a lower carboxylic acid, the corrosive action progressing in an ant nest-like manner from the surface of the tube in the thickness direction of the tube.

4. A heat transfer tube comprising the copper tube according to any one of claims 1 to 3, which is used as a heat transfer tube for air conditioning equipment or refrigeration equipment.

5. A refrigerant piping comprising the copper pipe according to any one of claims 1 to 3, which is used as a refrigerant piping for an air conditioner or a refrigeration device.

6. An air conditioner comprising the heat transfer tube according to claim 4.

7. A refrigeration appliance comprising the heat transfer tube according to claim 4.

8. An air conditioner comprising the refrigerant piping according to claim 5.

9. A refrigeration appliance comprising the refrigerant pipe according to claim 5.

Citation Information

Patent Citations

  • Highly corrosion-resistant copper pipe

    WO2014148127A1

  • High-corrosion-resistant copper pipe and method for producing same

    WO2018061270A1